The Mediating Role of Vietnamese Consumer Trust on Organic Food Consumption - HONG, NGUYEN BICH; TUYET, TRAN THI (The journal of contemporary issues in business and government, 2021)
Although consumers show high interest in as well as positive attitudes for organic food, the actual purchase of organic foods is regularly quite low. Previous studies have used the theory of planned behavior to explain consumers’ intention to buy organic food but have paid little attention on consumers’ trust. Literature also have emphasized that trust has been plating crucial role in making purchase decision. Hence, the study investigated the mediating role of consumer trust in making purchase decision on organic foods. A total of 159 customers from 3 supermarkets in Thai Nguyen province were elicited for the information needed in the study. Hayes’s bootstrapping procedure and corresponding SPSS macro was used to analyze the data. Results showed that trust has mediated between positive attitudes and intention to purchase organic foods. As subjective norm and perceived behavioral control have impacts on intention to buy organic food, trust also mediated these relationships. Therefore, in making purchase decisions, trust on the food has a major impact. Findings can be used to craft policies and innovations on organic foods to increase the trust of consumers thereby increasing organic consumption in Thai Nguyen, Vietnam.